Cheek and Chin Implants to Enhance Facelift Results - Kridel, Russell W. H.; Patel, Sagar (Facial Plastic Surgery, 2017)
The traditional rhytidectomy addresses facial and neck aging as it relates to soft tissue laxity. The modern volumetric facelift provides optimal results by addressing not only skin laxity but also the loss of volume secondary to tissue atrophy and bony resorption. While multiple techniques including fat grafting, dermal fillers, and tissue resuspension are used to correct the tissue loss, alloplastic midface augmentation remains the most permanent method. In our practice we often address midface cheek hollowness or atrophy with the placement of submalar implants at the time of rhytidectomy. In addition to midface volumetric rejuvenation, alloplastic chin implantation can help strengthen and further define a retrusive chin and weak jawline. In this article we discuss technique, indications, and benefits of performing alloplastic augmentation as an adjunct to rhytidectomy.
Keywords: facelift; rhytidectomy; implants; chin; cheek; malar; augmentation